(untitled) (LEGAL DIALOGICA, 2025)
This research aims to analyze the legal regulations for criminal acts of child exploitation committed by parents for social media content, and identify the factors that influence the occurrence of these criminal acts. This research uses normative legal research methods with data sources in the form of statutory regulations and secondary legal materials, such as literature studies and legal journals. The research results show that the legal regulation of child exploitation by parents for social media content is regulated in the Child Protection Law. Article 28B paragraph (2) and Article 34 paragraph (1) of the 1945 Constitution provide the legal basis for children’s rights, including the right to survival, growth and development without violence and discrimination. Apart from that, Article 76I of Law no. 23 of 2002 in conjunction with Law no. 35 of 2014 prohibits acts of economic and/or sexual exploitation of children. Violation of this provision is punishable by imprisonment for up to 10 years and/or a maximum fine of IDR 200,000,000.00 as regulated in Article 88 of the Child Protection Law. Abstrak: Penelitian ini bertujuan untuk menganalisis pengaturan hukum terhadap tindak pidana eksploitasi anak yang dilakukan oleh orang tua untuk konten media sosial, dsan mengidentifikasi faktor-faktor yang mempengaruhi terjadinya tindak pidana tersebut. Penelitian ini menggunakan metode penelitian hukum normatif dengan sumber data berupa peraturan perundang-undangan dan bahan hukum sekunder, seperti studi kepustakaan dan jurnal hukum. Hasil penelitian menunjukkan bahwa pengaturan hukum terhadap eksploitasi anak yang dilakukan oleh orang tua untuk konten media sosial diatur dalam Undang-Undang Perlindungan Anak. Pasal 28B ayat (2) dan Pasal 34 ayat (1) UUD 1945 memberikan landasan hukum mengenai hak-hak anak, meliputi hak atas kelangsungan hidup, pertumbuhan, dan perkembangan tanpa kekerasan dan diskriminasi. Selain itu, Pasal 76I UU No. 23 Tahun 2002 juncto UU No. 35 Tahun 2014 melarang tindakan eksploitasi ekonomi dan/atau seksual terhadap anak. Pelanggaran terhadap ketentuan ini diancam pidana penjara hingga 10 tahun dan/atau denda maksimal Rp200.000.000,00 sebagaimana diatur dalam Pasal 88 UU Perlindungan Anak.